2021
DOI: 10.3390/diagnostics11081396
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Cytomorphologic Features of Medullary Thyroid Carcinoma Using Different Staining Methods

Abstract: (1) Background: Accurate preoperative identification of medullary thyroid carcinoma (MTC) is challenging due to a spectrum of cytomorphologic features. However, there is a scarcity of studies describing the cytomorphologic features as seen on fine-needle aspiration (FNA) smears prepared using different staining methods. (2) Methods: We performed a retrospective study on MTC cases with available FNA slides from 13 hospitals distributed across 8 Asia-Pacific countries. The differences in the constitutive cytomor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Because diagnosing MTC based on cytomorphology alone is very challenging due to its rarity compared with PTC and the wide spectrum of cytologic features that often overlap with other neoplasms, the detection rate of FNAC in patients with MTC ranged from 12.5%–88.2% in a meta-analysis including 15 relevant studies and 641 MTC patients who underwent FNAC [ 24 ]. Seven cytomorphologic features were readily recognized in FNAC of MTC: high cellularity, cellular pleomorphism, plasmacytoid cells, round cells, discohesive cells, salt-and-pepper chromatin, and binucleation or multinucleation [ 25 ]. In another study, the following important cytologic parameters for MTC were also suggested: a dispersed cell pattern of polygonal cells, azurophilic cytoplasmic granules, and eccentric nuclei with coarse granular chromatin and amyloid [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because diagnosing MTC based on cytomorphology alone is very challenging due to its rarity compared with PTC and the wide spectrum of cytologic features that often overlap with other neoplasms, the detection rate of FNAC in patients with MTC ranged from 12.5%–88.2% in a meta-analysis including 15 relevant studies and 641 MTC patients who underwent FNAC [ 24 ]. Seven cytomorphologic features were readily recognized in FNAC of MTC: high cellularity, cellular pleomorphism, plasmacytoid cells, round cells, discohesive cells, salt-and-pepper chromatin, and binucleation or multinucleation [ 25 ]. In another study, the following important cytologic parameters for MTC were also suggested: a dispersed cell pattern of polygonal cells, azurophilic cytoplasmic granules, and eccentric nuclei with coarse granular chromatin and amyloid [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…55 Microfollicles show a uniform appearance; other features of these lesions include trabeculae, crowded cell groups, and isolated single cells in the background. 56 , 57 Cases with scanty colloids with a macro/microfollicular pattern are not covered by this term even if the smear is hypercellular. These lesions should be considered benign nodules or AUS/FLUS depending on the amount of colloid, microfollicle ratio, and cellularity.…”
Section: Cytomorphologic Features Of Thyroid Follicular Lesions and D...mentioning
confidence: 99%
“…Problematikus esetekben az immuncitokémia, szérum kalcitonin szint meghatározás és az FNA washout fluid kalcitonin szint elemzése, segíthet az MTC diagnózisában [25,26]. A kalcitonin szint jelentősége A vérben emelkedett kalcitonin szint és pajzsmirigy göb együttes jelenléte az MTC alapos gyanúját veti föl, de az MTC diagnosztikájában elsővonalbeli diagnosztikai módszer az FNAC, mely megbízhatóságát a kalcitonin immuncitokémiai kimutatásával jelentősen növelni lehet.…”
Section: Differenciáldiagnosztikai Megfontolásokunclassified